Pyrrolidinecarbodithioate as a planarity chuck in the search for cis-platin analogues of nickel: Spectral, single crystal X-ray structural, BVS, and CSM analysis of some planar nickel(II) mixed ligand complexes - Ramalingam, Kuppukkannu; Saravanan, Murugesan; Bocelli, Gabriele; Righi, Lara; Chumakov, Yurii; Cantoni, Andrea (European Journal of Chemistry, 2022)
[Ni(pyrdtc)(PPh3)(NCS)] (1), [Ni(pyrdtc)(4-MP)(NCS)] (2), [Ni(pyrdtc)(PPh3)(CN)]·H2O (3), [Ni(pyrdtc)(PPh3)2]ClO4 (4), and [Ni(pyrdtc)(P͡P)]BPh4·2H2O (5) [where pyrdtc: Pyrrolidine carbodithioate/S͡S, PPh3: Triphenylphosphine, 4-MP: Tri(4-methylphenyl)phosphine, dppe/P͡P: 1,2-Bis(diphenylphosphino)ethane] have been prepared from the parent bis-dithiocarbamate, [Ni(pyrdtc)]2 (6). The prepared compounds were characterized by electronic, IR, 1H, 13C, and 31P NMR spectra. In the IR spectra of the compounds, thioureide bands are observed at higher wavenumbers for the mixed ligand complexes 1-5 (1528-1540 cm-1) than the parent compound (1490 cm-1). Cyclic voltammetry showed an increasing order of reduction potentials: 5 << 1 2 < 3 < 4 << [Ni(pyrdtc)2] indicating an alleviation of electron density on nickel in the mixed complexes compared to the parent compound. Single crystal X-ray structure of the complexes displayed planar geometry around nickel which is in keeping with their diamagnetism. Bond Valence Sums calculated with the corrected Rij indicated the divalent nature of nickel with predominant covalent interactions. Continuous shape measure analysis of the mixed ligand chromophores stipulates a planar square environment around central nickel atom and deviation to tetrahedral or trigonal bipyramidal variants are absolutely negated. In this study, CSM analysis of cis-platin, a clinical anti-cancer agent, showed a comparable shape measure as those of the mixed ligand complexes 1-5. Hence, pyrrolidinecarbodithioate acts as a ‘chuck’ in compounds 1-5 to stabilize the planar square shape of the nickel chromophores and provides a suitable template to synthesize analogues of cis-platin.